2022
DOI: 10.1016/j.onehlt.2021.100367
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis in India: Comparing exposure amongst veterinarians, para-veterinarians and animal handlers

Abstract: The exposure to Brucella species is an occupational hazard for veterinary personnel in India. In our previous study, paraveterinarians and animal handlers were found to be at higher risk of being seropositive. In the present study, we further investigate comparative exposure risk to brucellosis amongst the veterinary professionals, identify risk factors, and evaluate the perceptions and practices towards using adequate personal protective equipment (PPE) while attending high risk veterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…The majority (59.8%) of the respondents did not undergo zoonotic disease screening in the past two years. Our findings are similar to those in a study conducted in the Northern part of the country (Punjab state) for brucellosis exposure among animal handlers, para veterinarians, and veterinarians, which reported that amongst the different tehsils (subdistricts), the veterinarians from Khanna were least likely to have been tested for brucellosis [ 34 ]. Screening of zoonotic diseases is very important for the health of the veterinarians; in a survey conducted among Australian veterinarians, wherein 44.9% ( n = 344) reported acquiring a zoonotic disease throughout their career [ 35 ], a higher percentage of positive for zoonoses reported among Australian veterinarians may be because of a higher percentage of screening of zoonotic diseases due to more awareness and availability of zoonotic diseases screening facility.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The majority (59.8%) of the respondents did not undergo zoonotic disease screening in the past two years. Our findings are similar to those in a study conducted in the Northern part of the country (Punjab state) for brucellosis exposure among animal handlers, para veterinarians, and veterinarians, which reported that amongst the different tehsils (subdistricts), the veterinarians from Khanna were least likely to have been tested for brucellosis [ 34 ]. Screening of zoonotic diseases is very important for the health of the veterinarians; in a survey conducted among Australian veterinarians, wherein 44.9% ( n = 344) reported acquiring a zoonotic disease throughout their career [ 35 ], a higher percentage of positive for zoonoses reported among Australian veterinarians may be because of a higher percentage of screening of zoonotic diseases due to more awareness and availability of zoonotic diseases screening facility.…”
Section: Discussionsupporting
confidence: 89%
“…Veterinarians must also be aware of their responsibility to protect colleagues and associated staff, particularly nontechnical staff who may not know or be unaware of how to recognize and adequately protect themselves from zoonoses. A study conducted in Punjab state India has underscored that lack of awareness about zoonotic diseases among animal handlers compared to paraveterinarians and veterinarians places them at higher risk to contract Brucella organism [ 34 ]. In Australia, veterinarians are legally required to provide this information [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, brucellosis is one of the seven most neglected diseases in the world, with an estimated 5,000,000 to 12,500,000 cases annually [ 10 , 11 ]. In addition, it is suspected to be a re-emerging disease that affects 500,000 new cases of human infection each year [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of doxycycline with rifampin or an aminoglycoside is effective in the treatment of brucellosis in humans. A retrospective study, such as this one, provides useful information regarding the trend of disease that can help formulate policies and strategies for the control and eradication of this occupationally hazardous disease, which is otherwise neglected [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%